Efektifitas Instagram @Gerakanbds Kampanye Boikot Produk Terafiliasi Israel - Sopiyah; Akhmad Rifa’i (Bahasa Indonesia, 2025)
This study analyzes the effectiveness of @gerakanbds as a boycott campaign medium against products affiliated with Israel, in the context of solidarity with Palestine. This study uses a descriptive qualitative approach by analyzing the content of Instagram posts and public responses through engagement metrics, such as the number of likes, comments, and shares. Using the Ostergaard campaign model, this study evaluates the content of the posts, user responses, and their impact on public awareness. The results show that the campaign succeeded in attracting attention and encouraging public participation to boycott products affiliated with Israel, as evidenced by the high social media interaction and economic impact on several brands included in the boycott list.